Implementasi Digitalisasi Sekolah Dasar sebagai Upaya Penguatan Kinerja Sekolah Dasar berbasis Transformasi Digital melalui Program PkM KKN - Wahyu Sri Ambar Arum; Arifin Maksum; Juhana Sakmal; Muhammad Ilham Darmawan; Neta Yolanda Putri; Nabillah Syahfa Septiani; Lia Handayani; Assifa Rohadatul Aisy; Leola Dewiyani; Arita Marini (Amaliah: Jurnal Pengabdian Kepada Masyarakat, 2025)
The teacher mentoring activity carried out through the Community Service Program (PkM) integrated with the Student Community Service (KKN) at SDN Pluit 03 primarily aims to support digital transformation in elementary education as a strategic effort to enhance school performance. This transformation is implemented by providing broad access to digital learning resources that can be accessed anytime and anywhere, thereby overcoming spatial and temporal limitations in the learning process. Additionally, the activity is specifically designed to strengthen the implementation of the Merdeka Curriculum, with an emphasis on project-based learning that promotes independent learning and knowledge exploration. In this context, strengthening digital literacy among teachers and students becomes crucial—not only to improve technological capabilities but also to broaden the range of richer and more varied teaching materials. The benefits of this empowerment initiative include improved teacher competencies in utilizing various digital tools and online learning resources, which in turn support the effectiveness of the teaching and learning process. Besides offering practical insights into digitalization, the program also fosters new habits among teachers to be more adaptive and open to the use of educational technology, enabling them to design lessons that are more responsive to student needs while remaining aligned with the flexible and student-centered principles of the Merdeka Curriculum.